Psychosocial barriers and cultural contexts in chemotherapy decision-making: a qualitative study of advanced lung cancer patients in China - Wang, Qing; Zhang, Jun; Hu, Mengying; Xu, Jiaojiao; Ai, Qiongqiong; Wei, Hequn; Yu, Jiao; Ma, Haiping (Frontiers in Oncology, 2025)
BackgroundShared Decision-Making (SDM) was developed within Western healthcare systems, which are characterized by cultural norms of individualism and low power distance, as a “patient-centered” medical decision-making model. Its applicability remains underexplored in collectivist societies like China, where family-centered decision-making and respect for authority shape medical encounters. Chemotherapy remains a cornerstone in the management of advanced lung cancer; however, the varied risk-benefit profiles of different therapeutic regimens often lead to decisional dilemmas and significant psychological burden in patients. This study investigates the chemotherapy decision-making experiences of advanced lung cancer patients in China to identify cultural barriers and inform the development of globally relevant SDM frameworks.MethodsThis study employs Colaizzi’s phenomenological approach and Hofstede’s cultural dimensions theory as the foundational theoretical framework. We conducted semi-structured interviews with 14 lung cancer patients and thematically analyzed the data through iterative coding and member validation. A purposive sample of 14 advanced lung cancer patients receiving chemotherapy was recruited from a tertiary hospital in Jiangxi Province, China.ResultsFrom the face-to-face conversations between patients and nursing staff, four main themes and 13 sub-themes were identified: Disease Treatment and Decision-making; Treatment Burden and Decision Conflict; Lifestyle Adjustment and Support Needs; Psychological Experience and Emotional Response.ConclusionsLung cancer patients face information barriers in the decision-making process and show high needs for decision-making assistance, psychological support, and social recognition. Healthcare professionals need to strengthen professional information support and communication, enhance patients’ enthusiasm for participating in decision-making, and pay attention to their intrinsic needs.